2012
DOI: 10.1212/wnl.0b013e31825dd383
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk factors for REM sleep behavior disorder

Abstract: Objective: Idiopathic REM sleep behavior disorder is a parasomnia characterized by dream enactment and is commonly a prediagnostic sign of parkinsonism and dementia. Since risk factors have not been defined, we initiated a multicenter case-control study to assess environmental and lifestyle risk factors for REM sleep behavior disorder.Methods: Cases were patients with idiopathic REM sleep behavior disorder who were free of dementia and parkinsonism, recruited from 13 International REM Sleep Behavior Disorder S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 21 publications
9
88
0
Order By: Relevance
“…However, as awareness has expanded, diagnosis is more frequent. To illustrate, the RBD study group quickly recruited 347 patients for an epidemiologic study, 33 well within sample size calculations (multiple centers would still be required for most trials).…”
mentioning
confidence: 99%
“…However, as awareness has expanded, diagnosis is more frequent. To illustrate, the RBD study group quickly recruited 347 patients for an epidemiologic study, 33 well within sample size calculations (multiple centers would still be required for most trials).…”
mentioning
confidence: 99%
“…Given the risk of misclassification of RBD status with this methodology, we used the term pRBD in this report. However, in prior studies with RBD diagnosed by PSG, a similar association between alcohol and RBD was also observed 4. To reduce the effects of potential misclassification of RBD status, we also did sensitivity analyses by excluding participants with RBD mimics.…”
Section: Discussionmentioning
confidence: 77%
“…A multicenter case‐controlled study of environmental risk factors for idiopathic RBD (iRBD), with 347 cases and 347 controls, found a nonsignificantly higher alcohol intake frequency in the case group, relative to the control group 4. Another community‐based study with 3635 participants showed a significant association between use of alcoholic beverage and pRBD, with an age‐ and sex‐adjusted OR of 2.16 (95% CI: 1.03, 4.50) for current drinkers, versus never drinkers 12…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations